2021
DOI: 10.1080/17530350.2021.1952098
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Relational Work: How gender shapes money attitudes and expectations of young adults

Abstract: We link the theory of gender performance to the perspective on the social meaning of money and relational work. Using longitudinal Panel Study of Income Dynamics data on young adult women and men, ages 18 through 24 in the U.S., we examine survey responses to different money-related situations. We question the expected gendertypical meanings of money, offering a more contextual understanding. Specifically, we find that when asked about the present, young women express that they worry more frequently about mone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 119 publications
0
5
0
Order By: Relevance
“…With regard to gender differences in tolerance of environmental protection cost, we found that men were more willing to spend more money, while women would rather sacrifice a little of their quality of life. These results reflect the difference in men's and women's attitudes toward money [42], in that women report that they worry more frequently about money than men do [43]. In this regard, everyone can contribute to environmental protection in different ways.…”
Section: Discussionmentioning
confidence: 76%
“…With regard to gender differences in tolerance of environmental protection cost, we found that men were more willing to spend more money, while women would rather sacrifice a little of their quality of life. These results reflect the difference in men's and women's attitudes toward money [42], in that women report that they worry more frequently about money than men do [43]. In this regard, everyone can contribute to environmental protection in different ways.…”
Section: Discussionmentioning
confidence: 76%
“…On the one hand, several studies found that women are more likely to view money as a source of anxiety and worries (Bandelj et al, 2021; Furnham & Grover, 2020; Furtner et al, 2021; Hayhoe et al, 2012; Oleson, 2004; Pereira & Coelho, 2019; Rimple, 2020; Simanjuntak, 2016). Indeed, women more frequently express distress and worry over money‐related matters and tend to express frustration when talking about it (Falahati & Paim, 2012; Prince, 1993; Rinaldi & Giromini, 2002; Tomek et al, 2013; Wernimont & Fitzpatrick, 1972).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the impact of stereotypic beliefs over money attitudes and behaviors is far from being explored empirically. Indeed, in the financial context, it has been proposed that the traditional gender role prescription ascribes household money management to women, whereas the financial market is mostly seen as a men playing field (Bandelj et al, 2021; Cohen et al, 2019; Kerber, 1988). Nevertheless, such a stereotypic content has not been deeply explored yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furnham (1984) found that while men were more obsessed with money than women, women were more security conscious and conservative than men. Bandelj et al (2021) found that women tend to worry more about money than men. Tang (1992) found that budgeting attitude was found more in females.…”
Section: Gender and Money Attitudes 21 Biological Gender And Money At...mentioning
confidence: 99%